EIB Complaints Mechanism Report 2019 - European Investment Bank (European Investment Bank, 2020)
The Complaints Mechanism report offers an overview of its actions in 2019. The main role of the Complaints Mechanism (EIB-CM) is to listen to citizens' concerns about an EIB Group project or activity, which can be about a wide range of issues. A large proportion of the complaints are about environmental and social impacts of EIB financed projects.In 2019, the EIB-CM registered 84 new cases, handled 173 cases and closed 113 of them. A number of highly complex cases were closed, including the Panama Canal Extension, Marišćina County Waste Management, Šoštanj Thermal Power Plant, and Reventazon Hydropower.This Activity Report describes these cases and other closed and ongoing cases. The report also covers the cases lodged with the European Ombudsman against the EIB Group. The report aims at giving a good idea of how the EIB-CM activities ensure the EIB Group remains accountable to the public.